1986
DOI: 10.1200/jco.1986.4.2.194
|View full text |Cite
|
Sign up to set email alerts
|

High complete response rate in children with advanced germ cell tumors using cisplatin-containing combination chemotherapy.

Abstract: A consecutive series of 13 children (five girls) with advanced malignant germ cell tumors (MGCTs) were treated with between four and seven (median, six) courses of cisplatin, bleomycin, and either vinblastine (BVP) or VP-16 (BEP). There were seven gonadal primaries (four testis, three ovary) and six at extragonadal sites (three sacrococcyx, two thoracic, one extradural). Total or subtotal removal of primary tumor was carried out in nine patients at diagnosis and two others after some chemotherapy. Clinical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
1
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 14 publications
0
23
1
1
Order By: Relevance
“…However, our data showed that chemotherapy regimen was not a significant predictor in FIGO stage I patients. In FIGO stage I, VAC produced a high proportion of cures, but in patients with metastatic disease the sustained remission rates of cisplatin-based chemotherapies are better than that of VAC (Pinkerton et al, 1986;Williams et al, 1989;Gershenson et al, 1990). Therefore, our results of multivariate analysis in FIGO stage I patients are not consistent with other reports concerning chemotherapy for ovarian YST.…”
Section: Clinicalfindingscontrasting
confidence: 56%
See 1 more Smart Citation
“…However, our data showed that chemotherapy regimen was not a significant predictor in FIGO stage I patients. In FIGO stage I, VAC produced a high proportion of cures, but in patients with metastatic disease the sustained remission rates of cisplatin-based chemotherapies are better than that of VAC (Pinkerton et al, 1986;Williams et al, 1989;Gershenson et al, 1990). Therefore, our results of multivariate analysis in FIGO stage I patients are not consistent with other reports concerning chemotherapy for ovarian YST.…”
Section: Clinicalfindingscontrasting
confidence: 56%
“…However, a combination of cisplatin, etoposide and bleomycin (BEP) (Smales & Peckman, 1987;Pinkerton et al, 1986;Gershenson et al, 1990;Williams et al, 1989) or cisplatin, vinblastine and bleomycin (PVB) (Bradof et al, 1982;Taylor et al, 1985;Einhorn & Donohue, 1977;Julian et al, 1980;Carlson et al, 1983;Davis et al, 1984) has been found to be even more effective and has produced remissions in patients with advanced-stage disease and in patients in whom other combinations of multiagent chemotherapy have failed (Bradof et al, 1982;Taylor et al, 1985;Einhorn & Donohue, 1977;Julian et al, 1980;Carlson et al, 1983;Davis et al, 1984;Smales & Peckman, 1987;Pinkerton et al, 1986;Williams et al, 1989;Gershenson et al, 1990). Cisplatin-based combination chemotherapy has revolutionised the treatment of patients with yolk sac tumour.…”
mentioning
confidence: 99%
“…This study demonstrates that, after cisplatin and carboplatin treatment the drug-target interaction is determined by both pharmacokinetic and, predominantly, cellular factors. Intrinsic differences between the two complexes, primarily reactivity, probably explain the lower adduct levels observed after carboplatin treatment.Keywords: cisplatin; carboplatin; Pt-DNA adduct; pharmacokinetics; child cancer Cisplatin and carboplatin are widely used in the treatment of solid tumours in childhood (Pinkerton et al, 1986;Pearson et al, 1992;Doz and Pinkerton, 1994). The activity and toxicity of cisplatin and carboplatin depend upon both pharmacokinetic and pharmacodynamic factors.…”
mentioning
confidence: 99%
“…Keywords: cisplatin; carboplatin; Pt-DNA adduct; pharmacokinetics; child cancer Cisplatin and carboplatin are widely used in the treatment of solid tumours in childhood (Pinkerton et al, 1986;Pearson et al, 1992;Doz and Pinkerton, 1994). The activity and toxicity of cisplatin and carboplatin depend upon both pharmacokinetic and pharmacodynamic factors.…”
mentioning
confidence: 99%
“…Dramatic improvement in cure rates of adults with malignant germ cell tumours using cisplatin-based regimens have been mirrored in paediatric practice (Einhorn & Donohue, 1977;Peckham et al, 1983;Williams et al, 1987;Pinkerton et al, 1986;Mann et al, 1987). With short-duration chemotherapy, non-mutilating surgery and avoidance of radiotherapy or alkylating agents, the majority of children, including many with metastatic MGCT, can be cured.…”
mentioning
confidence: 99%